TEST BLOOD GLUCOSE LEVELS USING ANTIDIABETIC DRUG IN white mice (RATTUS NOVERGICUS) - Nento, Nur Afni M (LP2M Universitas Bina Mandiri Gorontalo, 2023)
The purpose of this research is to find outpharmacological effects caused by antidiabetic drugs on White Rats (Rattus novergicus).In this study, we used white rats for antidiabetic test. This study was conducted, so that we know more about the effectiveness of antidiabetic drugs. In addition, as pharmacy students we must know which antidiabetic drugs are ideal and do not have side effects that are detrimental to users of these drugs. The main parameter of antidiabetic is blood glucose level. The method used is an experimental method using experimental animals in the form of white rats (Rattus novergicus). This research was conducted at the pharmacy laboratory of Bina Mandiri University, Gorontalo, the method used was an experimental method using experimental animals in the form of white rats (Rattus novergicus), where first white rats were fasted for 8 hours, then the rats' initial blood sugar was measured using a glucometer, after that 2 ml of 50% glucose was given. The results showed that the effect of antidiabetic drugs used, namely glibenclamide, metformin, glokovance on blood sugar levels in experimental white rats (Rattus novergicus) could provide a therapeutic effect that could lower blood sugar levels.